Dr.C. Rodrigo José Álvarez Cambras, a life of dedication to Orthopedics and Traumatology in Cuba - Royland Bejerano Durán; Lázaro Ernesto Horta Martínez; Melissa Sorá Rodríguez (Acta Médica del Centro)
Dr. Rodrigo José Álvarez Cambras was a renowned world-class cuban orthopedic surgeon, scientist and educator, deu to his various contributions to the level and improvement of the Orthopedics and Traumatology technique and rehabilitation process, as well as his promotion as an imminent professor. During his life he possessed titles, recognitions and decorations that puts him on the teaching hall of fame, cuban medicine and the cuban and world researches, he promoted this trio all over the world been an excellent performer with excellent results.